A retrospective cohort study evaluating demographic and clinical characteristics associated with use of seclusion in a London psychiatric intensive care unit. (1st April 2022) - Mark, Isabel; Bell, Darren; Lewis, William; Gleeson, Siobhan; O'Brien, Aileen
Seclusion is generally regarded as an important tool for aggression management in those admitted to a psychiatric intensive care unit (PICU). Nevertheless, it remains controversial with concerns regarding the ambiguity of who meets the threshold for seclusion. This study provides a detailed analysis of those who met the threshold and were secluded, whilst admitted to a London PICU, identifying key demographic features and clinical characteristics associated with seclusion use. All PICU admissions were examined over a one-year period (10 January 2020 – 9 January 2021). Data were collected retrospectively from patient electronic records. 125 patients met inclusion criteria for analysis, of whom 49 (39.2%) had been secluded during their admission and 76 (60.8%) had not. Those secluded included a higher proportion of patients with Black ethnicity (p = 0.004). A higher proportion of those secluded had been in employment prior to admission with fewer reporting long-term sick leave (p = 0.048). Seclusion was associated with a longer mean admission time (p = 0.02). Those requiring seclusion received higher doses of benzodiazepines during their admission (p = 0.009). Illicit drug use and forensic history were not found to be factors associated with seclusion use, in contrast to previous studies. Findings indicate that, within this cohort, seclusion is mostly associated with patient demographics and severity of illness.